UJI EFEKTIVITAS EKSTRAK BUNGA KENOP (Gomprhrena globosa L) TERHADAP LUKA BAKAR PADA HEWAN UJI KELINCI (Oryctolagus cuniculus) - Seri Agustini; Sari Wijayanti; Irma Novrianti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
ABSTRACT The plant that is believed by the public as a medicinal plant is Globe Amarant (Gomprena globosa L) which allegedly contains flavonoids and saponins compounds that can modulate wound healing acceleration. The flower has been shown to have an effect on wound healing in test animals, but so far there has been no research on the effectiveness of the knob flower on burns. Therefore, this study aims to identify the content of flavonoids and saponins in Kenop flowers and to see the effectiveness of healing burns in rabbits. The design of this study was an experimental study that used 5 groups of test animals, namely 2 control groups, and 3 groups of Kenop flower extract. Burn induction was performed using a 2x2 plate. The length of the wound was measured every 2 days using a caliper. Meanwhile, the identification test of flavonoid and saponin compounds was carried out using the forth and wilstatter methods. Based on the results of the study, it was found that the ethanol extract of the Kenop flower contains flavonoid and saponin compounds. The effectiveness test of the Knob flower extract on burns showed that the 30% extract group showed 92% wound healing with a wound diameter on the 14th day of 0.16; followed by a 20% extract group with a wound healing percentage of 84.3% with a wound diameter of 0.31 cm. The ethanol extract of the flower of the Kenop flower can heal burns at that concentration. Keywords: Kenop Flower, Flavonoids, Burns